Research on curing reaction kinetics and curing process of hydroxy-terminated polybutadiene (HTPB) propellants - Guo, Zhiming; Wang, Yiliang; Chiumsenti, Michele; Wu, Yuheng; Zhen, Shaocong; Liu, Hanwen; Rossi, Riccardo; Fu, Xiaolong (Scientific reports, 2025)
Hydroxyl-terminated polybutadiene (HTPB) propellants are high-performance solid propellants widely used in aerospace and military applications. By combining experimental and theoretical approaches, the curing process was analyzed using differential scanning calorimetry (DSC) to obtain reaction data at various heating rates. A thermochemical model and a finite-element model were developed to simulate the curing process, revealing the evolution of temperature and curing degree. The results indicate that higher heating rates significantly accelerate the curing reaction, reducing the curing time. The close agreement between the simulation and experimental data validates the reliability of the model. Future work could expand the model to include additional practical factors, such as material impurities and complex working conditions, to further optimize the HTPB propellant curing process.